The formation of urban centers under R&D and spillover externalities - Jan Kranich (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2009)
This paper proposes a model of urban agglomeration in conjunction with imperfect competition and endogenous product R&D of firms. The quality of differentiated manufacturing goods is a result of R&D services provided by research firms. Sectoral interactions are subject to spatially dependent transaction costs and (knowledge) spillover externalities. The paper analyzes the existence of fundamental city patterns with respect to R&D intensity and the degree of localization in knowledge production. The model features three equilibrium formations: a monocentric, a mixed, and a perfectly integrated pattern, whereas the R&D intensity always increases towards the city center. However, product quality and the corresponding R&D expenditures of firms are not necessarily increasing with the city size; a result, which also renders decisive implications of local innovation policy.
Keywords: R1; R14; 330; Bid-rent; Land Use; R&D; Externalities; Stadtzentrum; Agglomerationseffekt; Industrielle Forschung; Unternehmensdienstleistung; Spillover-Effekt; Städtische Bodennutzung; Theorie